INNOVATIVE WELL-BEING IN THE HIGHER EDUCATION SYSTEM ENHANCEMENT - Qarshiyev Azamat Rahmonivich (Journals Park Publishing, 2024)
This article outlines existing problems in improving the innovative well-being of the higher education system of the Republic of Uzbekistan, the acceptance of students in societies, the scientific well-being of teachers, and the existing material and technological base for the implementation of scientific research in higher education institutions.
Keywords: higher education system, higher education institution, scientific and educational activities, pedagogical staff, students, scientific well-being, innovative well-being.